Poincare based PPG signal analysis for varying physiological states - Kazmi , Syed Absar; Shah, Mansoor Hussain; Khan, Sheroz; Khalifa, Othman Omran; ., Muhammad Muzammil (IEEE, 2016)
This paper investigates the similarity and dissimilarity of the Photoplethysmography (PPG) signals depending upon the physiological conditions in nonlinear domain. Current paper also illustrates the variations in PPG signal for volunteers of age group among 20's (twenties). Easy Pulse analyzer Sensor module which operates on working principle of pulse oximetry which enables the photo sensing technique by detecting the infrared light penetrating through the respective part of body in this case is index finger. Afterwards it has been processed via series of filter stages comprised of low and high pass filters, an undistorted and adequate PPG signal has attained at the output of easy pulse analyzer. The frequency, shape, and amplitude ingredients of the PPG signal dominantly rely upon the physiological states and age factor. Furthermore, the signal is then fed to Arduino processing board which forms the provision of interfacing among easy pulse electronic module and personal computer in order to have the Graphical User Interface (GUI). The outcomes are quite obvious and are indicative of the physical states in terms of short and long term variability.